2004
DOI: 10.3998/ark.5550190.0005.531
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Schiff bases and 2,3-disubstituted-1,3-thiazolidin-4-one derivatives as antiinflammatory agents

Abstract: Dedicated to Professor Vincenzo Tortorella, University of Bari, in the occasion of his "fuori ruolo" status (received 14 Jan 04; accepted 12 May 04; published on the web 16 May 04) Abstract Two small sets of aromatic Schiff bases and 2,3-diaryl-1,3-thiazolidin-4-one derivatives have been prepared and tested for antiinflammatory and antinociceptive activities. The thiazolidinone derivatives have been obtained from the azomethines through the addition of α-mercaptoacetic acid. Both types of compounds displayed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Accordingly, a number of achiral bis-imines were prepared and used to generate the desired complex. While a number of methods have been reported to prepare Schiff bases by reacting an amine with a carbonyl compound [ 20 24 ], in our hands the reaction of 1,2-amines with aromatic aldehydes under these reaction conditions provided a mixture of mono and bis-Schiff bases. We therefore developed a new and efficient method for the preparation of bis-imines 3 by reacting ethane-1,2-diamine ( 1 ) with a number of aryl and heteroaryl aldehydes 2 in the presence of anhydrous FeCl 3 ( Scheme 2 , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, a number of achiral bis-imines were prepared and used to generate the desired complex. While a number of methods have been reported to prepare Schiff bases by reacting an amine with a carbonyl compound [ 20 24 ], in our hands the reaction of 1,2-amines with aromatic aldehydes under these reaction conditions provided a mixture of mono and bis-Schiff bases. We therefore developed a new and efficient method for the preparation of bis-imines 3 by reacting ethane-1,2-diamine ( 1 ) with a number of aryl and heteroaryl aldehydes 2 in the presence of anhydrous FeCl 3 ( Scheme 2 , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Melting points (uncorrected) were determined by an Electrothermal engineering LTD 9100 apparatus. IR spectra were recorded on a Perkin-Elmer model 543, the 1 H-and 13 C NMR spectra were obtained using Bruker Avance DRX 300 apparatus at 298 K. Chemical shifts (d) are reported in ppm and are referenced to the NMR solvent peak. Elemental analyses were carried out by a CHN- General procedure for the synthesis of compounds 3a-h in solvent-free conditions: A mixture of compound 1 (1.0 mmol) and an aromatic aldehyde (2.0 mmol) was magnetically stirred on a preheated oil bath at 100 °C for the appropriate time as indicated in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…8 Schiff bases have also been employed as chelating agents capable of coordinating metal ions to give complexes which serve as models for biological systems. 9,10 Conventionally, Schiff bases have been prepared by refluxing mixtures of amines and carbonyl compounds in an organic solvent, for example ethanol or methanol, 11 but variations are known, such as treatment of the same mixture at room temperature, refluxing the mixture in heptane in the presence of acetic acid 12 or azeotroping the mixture with benzene in a Dean-Stark apparatus in the presence of acid 13 and by using a template procedure. 14 In recent years, environmentally safer synthetic methods have received considerable attention and some solventfree protocols have been developed.…”
mentioning
confidence: 99%
“…[18,19] Thorough literature search revealed that 4-thiazolidinones are an important class of molecules due to their diverse biological profiles as COX-1 inhibitors, [20,21] non-nucleoside inhibitors of HIV-RT, [22] inhibitors of the bacterial enzyme MurB, [23] anti-histaminic [24] and anti-inflammatory agents. [25] In addition, thiazolidinone embedded molecular frameworks have also been investigated for their potential applications in the field of photonics, reversible optical data storage and photoswitching of optical elements. [26] Owing to the potential applications of porphyrins and 4-thiazolidinones, we successfully synthesized a series of meso-substituted porphyrinic thiazolidinones for the study of their optical characteristics.…”
Section: Introductionmentioning
confidence: 99%